POTENSI ARKEOLOGIS: GAMBAR CADAS KOMPLEKS GUA PRASEJARAH LIANG KABORI SULAWESI TENGGARA - Amaluddin Sope; Mahirta Mahirta (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The prehistoric cave art found in the Liang Kabori Prehistoric Cave Complex is significant and warrants attention to its potential. Since its initial discovery in the 1970s up to the present, data on its rock art—ranging from pigment colors to motif variations—has continued to expand with the discovery of new sites. This research employs a descriptive exploratory method. Data collection began with a literature review and field data gathering through survey techniques. The results reveal the richness of rock art found at each site, including variations in color, types of images, and quantity. The distribution of these images has the potential to shed light on the social life of the communities who created them, particularly in terms of religious aspects, the role of animals in their daily lives, their responses to the environment, the meaning of handprints (often placed on separate panels from other motifs), the use of boats, and the significance of kites in their society. Overall, the archaeological potential of this site opens opportunities for academic utilization and further research related to rock art, including conservation studies, given the ongoing deterioration of the images. This paper also reports five newly discovered rock art sites, bringing the total number of recorded sites to 43.